2008
DOI: 10.1080/13651500701784930
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum creatine kinase levels in psychiatric practice: differential diagnosis and clinical significance: A brief, practical guideline for clinicians

Abstract: Introduction. Elevated serum CK levels often occur in psychiatric in-patient practice. Although the majority of cases are benign and temporary, it is important to recognize and treat these conditions. Aims. To discuss the etiology, the clinical significance and the management of elevated creatine kinase levels in psychiatric in-patient practice, focusing on antipsychotic-induced rhabdomyolysis. To compare the pathogenesis and the clinical features of rhabdomyolysis and neuroleptic malignant syndrome. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…18 Periodic monitoring of clinical symptoms and creatine kinase levels has been recommended by several studies. 18,19 A systematic review of 42 published cases of MACKE – nine with clozapine treatment – found a prevalence of 2–7%. 20 MACKE was more frequent in males and in SGA-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Periodic monitoring of clinical symptoms and creatine kinase levels has been recommended by several studies. 18,19 A systematic review of 42 published cases of MACKE – nine with clozapine treatment – found a prevalence of 2–7%. 20 MACKE was more frequent in males and in SGA-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle damage was caused by activated neutrophils that infiltrate the damaged muscle tissue and release protease in response to liberated toxic cellular contents (9,12). Considering the induction of immune pathway by ethanol, one hypothesis should be contemplated: Corticosteroid administration helped diminish the inflammatory exacerbation of muscle damage and potentially decreased secondary immune-mediated muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol causes rhabdomyolysis through disruption of Adenosine triphosphates pump function, break down of the muscle membrane, alteration of the sarcoplasmic reticulum, sodium permeability and disrupting calcium homeostasis, inducing cytokine releasing the levels of "interleukin (IL) 1, IL-2, IL-6", and" tumor necrosis factor α" (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, serum CK evaluation is important in patients not only with symptoms of muscular pathologies such as muscle weakness, spasms, and myalgia, but also essential in patients using psychotropic medication. 8 Serum CK elevation in muscular pathologies characterized to be accompanied by increased serum levels of liver enzymes including aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, and aldolase 9 ; therefore, because our patient had an increased serum CK without any liver enzyme elevation and had not muscle-related symptoms, we excluded a muscle disorder for the diagnosis. We also excluded NMS because its characteristic findings that hyperthermia, muscle rigidity, autonomic dysfunction, altered mental status, and leukocytosis were not observed.…”
mentioning
confidence: 95%